Mesh migration following abdominal hernia repair: A case report, and literature review - Ali Jangjoo; Mohammad Ebrahim Kalantari; Tooraj Zandbaf (Babol University of Medical Sciences, 2022)
Background: Postoperative hematoma and seroma, foreign body reaction, infection, mesh rejection, and fistula formation are the complications associated with the use of surgical mesh. Mesh migration is a rare but serious and challenging complication after hernia repair. When this happens, infection, abscess, fistula, and bowel obstruction are the most common seaquelae. Case presentation: Our patient was a 62-year-old woman with a history of appendectomy 30 years ago and then underwent 3 incisional hernia repair surgeries which the last one was 5 years ago using laparoscopic IPOM. The patient was nominated for surgery with a diagnosis of recurrent incisional hernia. The patient underwent laparotomy and after enterolysis, a small bowel loop was seen that adhered to McBurney's region, which was released. There was a mass inside the small bowel. Resection and anastomosis of the involved intestine were performed. After enterotomy, it was determined that this mass was the mesh used in the previous surgery. Conclusion: Mesh migration is a rare consequence of incisional hernia repair with a prosthetic mesh. It can happen years after a hernia repair and it is additionally crucial to consider as a differential diagnosis in all patients who show unusual symptoms or abdominal pain.